Balanço de água em área de cultivo de soja no Leste da Amazônia - BISPO, Carlos José Capela (Universidade Federal do Pará, 2012)
The expansion of the agricultural frontier, driven mainly by soy cultivation (Glycine max (L) Merrill), covers a large regional extent and is highly important to understanding the changing face of Amazonia. A field observation experiment was established to study water balance components of the soy agriculture ecosystem and analyze the impact of the water balance associated with forest conversion. The experiment also evaluated the crop’s need for water according to its development phase. For the water balance study, the BRS Candeia cultivar was used along with its respective phenological phases. The experiment measured soil water storage, precipitation, plant cover water interception, superficial drainage of soil water, evapotranspiration (Etc), and water content retained by the soy plant. Water infiltration in the soil was also measured. Interception and superficial drainage were 45,9% and 1% of the precipitation, respectively. The greatest evapotranspiration occurred during the flowering phase (R1-R2) with a gradual decline in values until crop harvest and a cycle average of 3,80mm.day-1, which was very similar to that found in forest. The period between the vegetative phase (V) and fruiting (R3-R4) was when the plant presents the greatest percentage of water, declining gradually during the grain-forming phase (R5). Overall, no water deficiency occured in the mean soil water balance. Precipitation was greater than the amount necessary to compensate for evapotranspiration and supply adequate water storage, creating a surplus of water in the soil.